1996
DOI: 10.1006/viro.1996.0036
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Gene Expression Is Activated by X Protein but Repressed by p53 Tumor Suppressor Gene Product in the Transient Expression System

Abstract: Hepatitis B virus (HBV) X gene is known to exhibit a transcriptional activation function and is considered to play a major role in hepatocarcinogenesis. We determined a 20-bp promoter element for the HBV X gene transcription and found a binding protein to this promoter element, designated as an X-PBP. We then examined the effects of HBV X protein and p53 tumor suppressor gene product on X gene transcription from the 20-bp promoter element using the transient expression technique. Activity of the X gene promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…The basal promoter of the X gene was found to be negatively regulated by transfected p53 gene, but not by its mutants. Moreover, when the p53 gene was transfected together with the X gene, the negative eect of p53 gene was counteracted by X protein coexpression (Takada et al, 1994b(Takada et al, , 1996. On the other hand, growth regulatory genes, such as p21WAF1/Cip1 (El-Deiry, 1994), cyclin G (Okamoto and Beach, 1994), the muscle creatine kinase gene promoter (Weintraub et al, 1991;Zambetti et al, 1992) or the PG13-CAT (Kern et al, 1991;Wang et al, 1994), were positively regulated under similar conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basal promoter of the X gene was found to be negatively regulated by transfected p53 gene, but not by its mutants. Moreover, when the p53 gene was transfected together with the X gene, the negative eect of p53 gene was counteracted by X protein coexpression (Takada et al, 1994b(Takada et al, , 1996. On the other hand, growth regulatory genes, such as p21WAF1/Cip1 (El-Deiry, 1994), cyclin G (Okamoto and Beach, 1994), the muscle creatine kinase gene promoter (Weintraub et al, 1991;Zambetti et al, 1992) or the PG13-CAT (Kern et al, 1991;Wang et al, 1994), were positively regulated under similar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although normal X protein is known to activate transcription of many genes through various enhancer elements, such as AP-1 and AP-2 binding sequences in SV40 enhancer (Seto et al, 1990), kB-like sequences in HIV-LTR (Siddiqui et al, 1989;Twu et al, 1989) and the 26 bp XRE (X-responsive element) in the HBV enhancer I (Faktor and Shaul, 1990), our previous data indicate that the X responsive element is also present in the X gene basal promoter (Takada et al, 1996). In addition, it was reported that X protein contained the Kunitz inhibitor (KI) domain-like region against serine proteases, which is indispensable for activation function of the X protein (Takada et al, 1994a;Takada and Koike, 1990b) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because, HCV belongs to RNA virus, and is not integrated into host hepatocyte DNA which causes the mutation. Whereas, concerning HBV, it is well known that integrated HBV genome into hepatic DNA may play an important role in hepatocarcinogenesis (1)(2)(3).…”
Section: Hepatocellular Carcinoma (Hcc) Is Currently a Very Common Mamentioning
confidence: 99%
“…33 Viral promoters include the HSV-tk gene promoter, the Simian virus 40 promoter, the polyoma virus promoter, the cytomegalovirus promoter, the Rous sarcoma virus promoter, the hepatitis B virus core promoter, and various retroviruses LTR promoters. [45][46][47][48][49][50][51][52][53] Although p53 can repress promoters via several mechanisms, accumulating evidence suggests that it may also repress transcription through recruitment of histone deacetylases (HDACs) and chromatin remodelling. 33 An indication that p53 may repress promoters through chromatin structure alteration was obtained from studies using trichostatin A (TSA), an HDAC inhibitor.…”
Section: Discussionmentioning
confidence: 99%